THE EFFECT OF NEED FOR COGNITION AND NEED FOR AFFECTION ON THE INTENTION OF SPREADING FAKE NEWS - Gumelar, Gumgum; Erik, Erik; Maulana, Herdiyan (SCAD Independent, 2020)
The aim of this study is to determine the effect of the need for cognition and the need for affection towards the intention of spreading fake news. This research used an experimental design by giving the participants some manipulations in the form of fake news. The study examined whether the participant spreads the news provided based on their different need orientations. The results of this study indicate that there was a significant relationship between the need for affection and the need for cognition in terms of spreading false news. This study also investigated the variation of the tendency to spread the news based on both need scores. Although predictions are related to participants who have high or low scores who tend to spread false news, further research is needed.